A Gentle Introduction to Machine Learning for Natural Language Processing: How to Start in 16 Practical Steps. Issue 2 (February 2015) - Hladka, Barbora; Holub, Martin
Abstract We present a gentle introduction to machine learning in natural language processing. Our goal is to navigate readers through basic machine learning concepts and experimental techniques. As an illustrative example we practically address the task of word sense disambiguation using the R software system. We focus especially on students and junior researchers who are not trained in experimenting with machine learning yet and who want to start. To some extent, machine learning process is independent on both addressed task and software system used. Therefore readers who deal with tasks from different research areas or who prefer different software systems will gain useful knowledge as well.